Community Structure of Gastropods in the Bay of Muara Angke Teluk Jakarta - Rina Wahyu Witra; Nur El Fajri; Muhammad Fauzi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Muara Angke Bay is home to many types of gastropods. The purpose of this study was to determinethe structure of the gastropod community in the waters of the river. This research was conducted inJuly-September 2021. There are 3 observation stations including the estuary area (station 1),fisherman settlement area (station 2), and port area (station 3). There are 3 quadrants of gastropodsamples and water quality was taken 3 times in 1 week. Gastropod samples were taken by handcollecting or by hand and given 10% formalin as a preservative. Parameters measured includeddensity, diversity index, and gastropod dominance index. Water quality parameters includetemperature, pH, current velocity, depth, and dissolved oxygen. The types of gastropods foundduring the study were Melanoides sp and Pomacea sp. The density of gastropod species rangedfrom 1.319 to 2.748 ind/m, the diversity index ranged from 2.59 to 3.47, and the dominance indexranged from 0.27 to 0.34. Water quality parameters: temperature ranged from 29-300C, currentvelocity 15.18-24.91 cm/sec, depth 12.2-26.5 cm, pH 6 and dissolved oxygen ranging from 4.5 to5.6 mg/L. From the data obtained, it can be concluded that the gastropod community structureobtained is in moderate criteria.